Shifting seasonality of cyclones and western boundary current interactions in Bay of Bengal as observed during Amphan and Fani - Sourav Sil (Nature Portfolio, 2021)
Abstract In recent years, the seasonal patterns of Tropical Cyclones (TC) in the Bay of Bengal have been shifting. While tropical depressions have been common in March–May (spring), they typically have been relatively weaker than the TCs during October–December. Here we show that the spatial pattern of recent warming trends during the last two decades in the southwestern Bay has allowed for stronger springtime pre-monsoon cyclones such as Amphan (May 2020, Super Cyclone) and Fani (April–May 2019, Extremely Severe Cyclone). The tracks of the pre-monsoon cyclones shifted westward, concurrent with an increasing rate of warming. This shift allowed both Fani and Amphan tracks to cross the northeastward warm Western Boundary Current (WBC) and associated warm anti-cyclonic eddies, while the weaker Viyaru (April 2013, Cyclonic Storm) did not interact with the WBC. A quantitative model linking the available along-track heat potential to cyclone’s intensity is developed to understand the impact of the WBC on cyclone intensification. The influence of the warming WBC and associated anti-cyclonic eddies will likely result in much stronger springtime TCs becoming relatively common in the future.